Eomes is sufficient to regulate IL-10 expression and cytotoxic effector molecules in murine CD4+ T cells - Thelen, Benedikt; Schipperges, Vincent; Knörlein, Paulina; Hummel, Jonas F.; Arnold, Frederic; Kupferschmid, Laurence; Klose, Christoph S. N.; Arnold, Sebastian J.; Boerries, Melanie; Tanriver, Yakup (Frontiers in Immunology, 2023)
The T-box transcription factors T-bet and Eomesodermin regulate type 1 immune responses in innate and adaptive lymphocytes. T-bet is widely expressed in the immune system but was initially identified as the lineage-specifying transcription factor of Th1 CD4+ T cells, where it governs expression of the signature cytokine IFN- γ and represses alternative cell fates like Th2 and Th17. T-bet’s paralog Eomes is less abundantly expressed and Eomes+ CD4+ T cells are mostly found in the context of persistent antigen exposure, like bone marrow transplantation, chronic infection or inflammation as well as malignant disorders. However, it has remained unresolved whether Eomes executes similar transcriptional activities as T-bet in CD4+ T cells. Here we use a novel genetic approach to show that Eomes expression in CD4+ T cells drives a distinct transcriptional program that shows only partial overlap with T-bet. We found that Eomes is sufficient to induce the expression of the immunoregulatory cytokine IL-10 and, together with T-bet, promotes a cytotoxic effector profile, including Prf1, Gzmb, Gzmk, Nkg7 and Ccl5, while repressing alternative cell fates. Our results demonstrate that Eomes+ CD4+ T cells, which are often found in the context of chronic antigen stimulation, are likely to be a unique CD4+ T cell subset that limits inflammation and immunopathology as well as eliminates antigen-presenting and malignant cells.